2020
DOI: 10.3329/bjns.v9i2.44889
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Low Back Pain among Medical Professionals Working In Selected Tertiary Hospitals in Dhaka City

Abstract: Background: Health care workers are most frequently suffering from lower back pain. Objective: The purpose of the present study was to determine the prevalence and the effects of low back pain among health care providers working in Dhaka city. Methodology: This descriptivecross sectional study was conducted in Department of Neurosurgery at National Institute of Neurosciences & Hospital, Dhaka, Bangladesh from July 2012 to June 2013 for a period of one (1) year. The physicians and nurses who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Socio-demographic measures and determinants of LBP Socio-demographic information included age (later categorised into two categories: 18-40 years and >40 years), profession (farmer/rickshaw puller/office worker), marital status (married/unmarried), education qualification (illiterate/can sign only/institutional education), family category (up to four members/more than four members), monthly family income (up to 15 000 Bangladeshi taka (BDT)/15 000-30 000 BDT/more than 30 000 BDT), 15 residence (village/city), body mass index (BMI) (underweight/normal-weight/overweight), regular physical activity (yes/no), smoking (yes/no), depressive symptoms (yes/no), sleep duration (up to 6 hours/ more than 6 hours), training for own profession (yes/ no), daily working hours (4-8 hours/9-12 hours), 4 duration of working (<5 years/>5 years), chronic disease (yes/ no), family history of LBP (yes/no), numbness in legs or Open access feet (yes/no), healthcare access in the local area (yes/ no), prior knowledge of LBP (yes/no). LBP was evaluated using the Nordic questionnaire (Do you have lower back pain (prolonged or sudden sensations of discomfort, pain, or trouble in the lower back or buttock regions within the 12 months leading up to the questionnaire's completion), yes/no) modified and adapted to the population of Bangladesh.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Socio-demographic measures and determinants of LBP Socio-demographic information included age (later categorised into two categories: 18-40 years and >40 years), profession (farmer/rickshaw puller/office worker), marital status (married/unmarried), education qualification (illiterate/can sign only/institutional education), family category (up to four members/more than four members), monthly family income (up to 15 000 Bangladeshi taka (BDT)/15 000-30 000 BDT/more than 30 000 BDT), 15 residence (village/city), body mass index (BMI) (underweight/normal-weight/overweight), regular physical activity (yes/no), smoking (yes/no), depressive symptoms (yes/no), sleep duration (up to 6 hours/ more than 6 hours), training for own profession (yes/ no), daily working hours (4-8 hours/9-12 hours), 4 duration of working (<5 years/>5 years), chronic disease (yes/ no), family history of LBP (yes/no), numbness in legs or Open access feet (yes/no), healthcare access in the local area (yes/ no), prior knowledge of LBP (yes/no). LBP was evaluated using the Nordic questionnaire (Do you have lower back pain (prolonged or sudden sensations of discomfort, pain, or trouble in the lower back or buttock regions within the 12 months leading up to the questionnaire's completion), yes/no) modified and adapted to the population of Bangladesh.…”
Section: Methodsmentioning
confidence: 99%
“…Various environmental and personal factors influence the onset and progression of LBP 3. It is estimated that 70–85% of adults experience at least one episode of LBP in their lives, making it a significant health concern 4. LBP not only affects productivity and quality of life but also leads to substantial direct and indirect costs, making it a leading cause of musculoskeletal disability globally.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also found a significant influence of past LBP complaints (Sopajareeya, 2021;Mahmud et al, 2021), poor body posture (Islam et al, 2020;Wong et al, 2010), prolonged standing (Nair, 2020), walking (Qareeballa et al, 2018), and weight (Suliman, 2018) on LBP occurrences. Removing patients, lifting heavy objects, gender, age, stress, type of work, workplace environment, and work duration were declared to influence LBP occurrences since three or more articles have found the effect of those variables.…”
Section: Risk Factormentioning
confidence: 96%
“…In Saudi Arabia, manual patient removal has been found to be related to and significantly influences LBP occurrence (Islam et al, 2020;Nair, 2020;Wong, Teo, and Kyaw, 2010;Sopajareeya, 2021). In addition, it can lift heavy objects (Qareeballa et al, 2018;Islam et al, 2020;Nair, 2020;Wong et al, 2010).…”
Section: Risk Factormentioning
confidence: 99%
See 1 more Smart Citation